Penerapan Metode Klasifikasi dan Seleksi Fitur untuk Meprediksi Minat Studi dan Karir Siswa: (Studi Kasus SMK Se-Kabupaten Kudus) - Aditia Candra Kusuma; Eka Ardhianto (Pusat Riset dan Inovasi Nasional, 2025)
Every year, vocational high schools in Kudus Regency produce competitive graduates in the national and international job markets, because vocational high school graduates must be equipped with technical skills and soft skills. However, students face a dilemma in determining the next step in choosing a study interest or career. In addition, several factors influence student interests, one of which is family beckground, so that students who were initially sure will become unsure of their interests. Therefore, the purpose of this study is to classify student interests. The use of classification methods with the naïve bayes algorithm and feature selection with forward selection was chosen in this study. Classification model testing was carried out three times with a comparison of training data and test data (90:10, 80:20, and 70:30), where the results obtained had an average accuracy value of 72.85%, an averagr precision velue of 77.75%, and an average recall value of 86.43%. the classification results are continued with the application of forward selection to find influential attributes, and the results of feature selection show that major attribute, achievement attributes, and mathematics value attributes have an influence on student interest.